Social media addiction and its impact on employee performance - Tuti Setyorini; Janri Manafe; Jappy Fanggidae (Enrichment : Journal of Management, 2022)
This study aims to investigate the impact of social media addiction on employee performance. Literature in the field has shown that social media addiction among employees may determine their performance in the workplace. We go further by assessing the mechanism within the relationship between social media addiction and employee performance. We assumed that social media addiction influences employees’ emotions such as happiness and job stress which eventually affect employees’ job performance. In order to achieve such goals, we used quantitative methods. The collected data were analyzed using the principles of Structural Equation Modelling. We also discussed the theoretical and practical implications of the present study.